Impact of Freeze-Dried Amnion Membrane and Human Amnion Stem Cell Seeding on TGF-B and Collagen Type III in Vesicovaginal Fistula - Sihotang, Jojor; Mardiyan, Eighty; Widjiati, Widjiati; Hidayatullah, Amiruddin (Indonesian Journal of Obstetrics and Gynecology, 2024)
Objective: to analize how freeze-dried amniotic membrane and human amniotic stem cell seeding affect TGF B and type III collagen expression in suturing a New Zealand rabbit vesicovaginal fistula model. Metode: This experimental study employed New Zealand rabbits and a vesicovaginal fistula model with a post-test only control group design. The rabbits were divided into 3 groups: vesicovaginal fistula suturing alone, suturing with freeze-dried amniotic membrane, and suturing with freeze-dried amnion-seeded stem cells. After 7 days of treatment, specimens near the repaired vesicovaginal fistula were collected for immunohistochemical analysis of TGF B and collagen type III expression. Result: TGF B expression was significantly higher in the freeze-dried amniotic membrane with stem cell seeding group (p=0.001) compared to the freeze-dried amniotic membrane without stem cell seeding group (p=0.017) and the suturing-only group (p=0.049). Additionally, type III collagen expression was significantly elevated in the freeze-dried amnion membrane and stem cell seeding group (p=0.001) compared to the freeze-dried amnion group without stem cell seeding (p=0.09) and the suturing-only group (p=0.026). Conclusion: The expression of TGF B and type III collagen was higher in rabbits with vesicovaginal fistulas treated using freeze-dried amnion and amniotic stem cell seeding compared to those without amniotic stem cell seeding and vesicovaginal fistula suturing alone. Keywords: Vesicovaginal Fistula, Freeze-dried Amnion, Stem cell